Lamiaceae endémicas del Perú - Rodriguez, Maritza (2006)
The Lamiaceae are represented in Peru by around 21 genera and 190 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly herbs and shrubs. Here we recognize 57 endemic species in nine genera. Salvia is the genus with the largest number of endemic species. Endemic Lamiaceae species are found mostly in the Mesoandean and Very Humid Montane Forest regions, between 1500 and 4250 m elevation. Seven endemic species of Lamiaceae have been recorded to date in the Peruvian protected areas system.